Electrochemical cell balancing using a full-bridge multilevel converter and pseudo-open circuit voltage measurements - Chatzinikolaou, E (Institute of Electrical and Electronics Engineers, 2016)
This paper presents a method of estimating relative electrochemical cell state of charge in a cascaded full-bridge multilevel converter. The control flexibility of the multilevel topology is used to introduce an idle state during which the cell is temporarily removed from the load current path in order to make a pseudo-open circuit measurement of cell voltage. This measurement is used to estimate relative cell state of charge. The duty cycle of each cell is adjusted based on this measurement in order to achieve balancing. The validity of the proposed balancing scheme is demonstrated through three different experiments: discharging of twelve cells without balancing, discharging the cells by implementing a balancing scheme without the idle state for voltage measurement and discharging with the proposed balancing incorporating the idle state. The results show that the proposed method can extract the entire capacity from each cell despite large imbalance of 28% in initial cell state of charge, extending the effective capacity of the system by 19%.